Commodification and Authenticity of the Panji Bobung Mask Traditional Art In Putat Tourism Village - Slamet Subiyantoro; Kristiani Kristiani; Dwi Maryono; Dimas Fahrudin; Yasin Surya Wijaya (Universitas Andalas, 2022)
Panji has evolved into a well-known folklore and an art form that provides a source of income for its conservationists. The purpose of this research is to examine the commodification and authenticity of Topeng Panji art in Bobung as an effort to face the era of globalization and localize the nation's cultural arts. The research was conducted in Bobung, Putat, Patuk, Gunung Kidul, Yogyakarta. This study uses a qualitative descriptive approach with a single case strategy. Data is sourced from informants, venues and documents/archives collected with in-depth interview techniques, participatory observations, and content analysis. The validity of the data is tested by source triangulation techniques and informant reviews. Data analysis is conducted with interactive analysis models with data reduction, data display, and verification procedures. The results of this study show that the Commodification of Topeng Panji is based on the increasing and complex needs of the community where the source of income from agriculture and plantations is not enough. The authenticity or art of Topeng Panji tradition in Bobung is maintained by the community by introducing it to the younger generation from an early age.